Angústia e conhecimento: uma reflexão a partir dos pensadores religiosos Franz Rosenzweig, Sören Aabye Kierkegaard, e Qohélet - Guarnieri, Maria Cristina Mariante (2006)
This thesis studies angst as a religious philosophical concept beside the importance of the religious thinker as a comprehension method for religion. Regarding this, it takes as object the religious thinkers Franz Rosenzweig, Sören A. Kierkegaard and the wise man Qohelet, of the Old Testament, whose reflections indicate the presence of angst. The hypothesis that guides this work is that, in these thinkers, this presence, due to the relationship with the transcendent, manifests itself as conceptual tension which produces knowledge. In view of this hypothesis, the intention is to discuss the possibility of building knowledge from religion itself. Angst, then, is the affection that, in these authors, indicates a tension between immanence and transcendence, realizing the human finitude and the infinite possibility, the absolute lack of meaning and the establishment of a multiplicity of meanings. It is a productive agony that serves as hard task in the search for knowledge. Giving priority to the subjectivity and the concreteness of the existence, the authors here worked make an effort to understand the human being, unique is his or her suffering. The angst as key for thinking about the human condition is born from the perception of its own aporia, discovery starting from the first inquiry about the meaning of life